Penerapan Next.js dan GraphQL dalam Pengembangan Mobile Web Sistem Informasi Manajemen Puskesmas - Dwi Aulia Anugerah; Kosasi, Sandy (CSRID (Computer Science Research and Its Development Journal), 2024)
This research focuses on the development of a Mobile Web-based Puskesmas Management Information System (SIMPUS) motivated by the need for the Puskesmas Rawat Inap Jungkat to improve information services and data management. The problem being faced by the Puskesmas Rawat Inap Jungkat is that the management of patient data visiting the health center is still manual and is done repeatedly, which results in the efficiency and effectiveness of services being hampered and data redundancy. SIMPUS mobile web development applies Next.js for the front-end and Laravel for the back-end, with GraphQL as the data retrieval protocol. This system is designed to simplify the patient registration process, polyclinic data management from registered patients, and efficient service management. This research uses the Design Science Research (DSR) method with data collection techniques in the form of observations, interviews, and documentation studies to develop a mobile web information system and puskesmas management that focuses on patient registration until the patient's data that registers directly enters the intended polyclinic. The System Modeling with Unified Modeling Language (UML) with White-Box testing to ensure system functionality. The results of the study are expected to make a positive contribution in improving the quality of health services at the Puskesmas Rawat Inap Jungkat, increasing operational efficiency and effectiveness, and facilitating access to information for patients and health center staff.